Feasibility of Group Schema Therapy for Outpatients with Severe Borderline Personality Disorder in Germany: A Pilot Study with Three Year Follow-Up - Fassbinder, Eva; Schuetze, Maren; Kranich, Annika; Sipos, Valerija; Hohagen, Fritz; Shaw, Ida; Farrell, Joan; Arntz, Arnoud; Schweiger, Ulrich (Frontiers in Psychology, 2016)
Borderline Personality Disorder (BPD) is a severe, challenging to treat mental disorder. Schema therapy (ST) as an individual therapy has been proven to be an effective psychological treatment for BPD. A group format of ST (GST) has been developed and evaluated in a randomized controlled trial in the United States and piloted in The Netherlands. These results suggest that GST speeds up and amplifies treatment effects of ST and might reduce delivery costs. However, feasibility in the German health care system and with BPD patients with high BPD severity and comorbidity, and frequent hospitalization, has not been tested to date. We investigated GST in ten severely impaired, highly comorbid female patients with BPD, that needed frequent hospital admission. Patients received an outpatient ST-treatment program with weekly group and individual sessions for one year. Outcome measures including BPD severity, general psychopathology, psychosocial functioning, quality of life, happiness, schemas and modes, and days of hospitalization were assessed at the start of treatment and six, twelve and 36 months later with semi-structured interviews and self-report measures. We observed significant decreases in severity of BPD symptoms, general symptom severity, dysfunctional BPD-specific modes and schemas, and days of hospitalization. Functional modes, quality of live and happiness improved. The results of this feasibility study are promising and encourage further implementation of ST outpatient treatment programs even for patients with severe BPD and high hospitalization risk. However, small sample size and the missing of a control group do not allow the generalizability of these findings.